DETERMINATION OF THE FREQUENCY CHARACTERISTICS OF THE GEOLOGICAL ENVIRONMENT AT CONSTRUCTION SITES USING STATISTICAL MODELING OF SEISMIC NOISE ON THE EXAMPLE OF OBSERVATIONS IN ODESSA - Kendzera, O.; Vyzhva, Z.; Fedorenko, K.; Vyzhva, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The task of implementing the statistical simulation of random processes and fields on the plane with a uniform grid interpolation in seismological research needs to determine the frequency characteristics of the geological environment at construction sites is considered. The algorithms for statistical modeling and fields based on interpolation schedules and based on the results of statistical analysis of seismic waves recorded and estimates of error approximation of random processes and fields are formulated. The models for statistical modeling adequate implementations seismograms noise in the cases of one and two variables are conctructed.